P-9 α-TCP/Te-CPセメントの根管充填用シーラーへの応用 : 病理組織学的評価(セメント,一般講演(ポスター発表),第65回日本歯科理工学会学術講演会) - 神山 智佳子; 武田 進平; 河野 哲; 堀口 敬司; 玉置 幸道; 吉田 隆一 (日本歯科理工学会誌, 2015)
The aim of this study was to investigate the characteristics of experimental root canal sealing material. Bi_2O_3 fine powder was prepared in less than 25 μm and blended with α-TCP/Te-CP. The experimental sealer was severally mixed with two kinds of solutions (disodium hydrogen phosphate, sodium chondroitin sulfate) and then histopathological conformity as a biomaterial was examined. When filling the experimental sealer with each solution, suitable biological response with bone-like tissue regeneration was observed after 14 days. In contrast, a commercial product based on calcium hydroxide showed the undesirable biocompatibility.